2005
DOI: 10.2337/diabetes.54.6.1873
|View full text |Cite
|
Sign up to set email alerts
|

Type A Insulin Resistance Syndrome Revealing a Novel Lamin A Mutation

Abstract: Particular forms of polycystic ovary syndrome with severe hyperandrogenism, acanthosis nigricans, and marked insulin resistance, defining the type A insulin resistance syndrome, are due to insulin receptor gene mutations. However, the majority of affected individuals do not have such mutation, arguing for the genetic heterogeneity of this syndrome. The familial partial lipodystrophy of the Dunnigan type, one of the diseases due to mutations in the lamin A/C (LMNA) gene, is characterized by a lipodystrophic phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 29 publications
4
44
1
2
Order By: Relevance
“…The cases described here, similarly to that described previously by Young et al (29), illustrate clearly that monogenic insulin resistance caused by a primary defect in adipose tissue development and function, like insulin resistance caused by primary insulin signalling defects, may produce PCOS. Indeed, hyperandrogenism and oligomenorrhoea are the commonest reasons for presentation to a medical practitioner of patients with monogenic insulin resistance, and careful clinical examination for acanthosis nigricans or abnormal adipose tissue topography are key components of the initial evaluation of any patient with PCOS.…”
Section: Discussionsupporting
confidence: 86%
“…The cases described here, similarly to that described previously by Young et al (29), illustrate clearly that monogenic insulin resistance caused by a primary defect in adipose tissue development and function, like insulin resistance caused by primary insulin signalling defects, may produce PCOS. Indeed, hyperandrogenism and oligomenorrhoea are the commonest reasons for presentation to a medical practitioner of patients with monogenic insulin resistance, and careful clinical examination for acanthosis nigricans or abnormal adipose tissue topography are key components of the initial evaluation of any patient with PCOS.…”
Section: Discussionsupporting
confidence: 86%
“…9696 c.746G>A 4 p.R249Q Missense Coil 2a (Benedetti, et al, 2007;Ki, et al, 2002;Muchir, et al, 2004;Raffaele Di Barletta, et al, 2000;Rudenskaya, et al, 2008;Vytopil, et al, 2003) (Onishi, et al, 2002) 2570 c.1072G>A 6 p.E358K Missense Coil 2b (Benedetti, et al, 2007;Mercuri, et al, 2004;Quijano-Roy, et al, 2008) (Benedetti, et al, 2007;Bonne, et al, 1999;Brette, et al, 2004;Colomer, et al, 2002;Fidzianska and Glinka, 2006;Golzio, et al, 2007;Muchir, et al, 2004;Raffaele Di Barletta, et al, 2000;Vytopil, et al, 2003) (Arbustini, et al, 2005) 7288 c.1580G>C 9 p.R527P Missense Tail (Ig-fold) (Benedetti, et al, 2007;Bonne, et al, 1999;Raffaele Di Barletta, et al, 2000;van der Kooi, et al, 2002) 1527 c.1583C>A 9 p.T528K Missense Tail (Ig-fold) (Benedetti, et al, 2007;Fokkema, et al, 2005;Raffaele Di Barletta, et al, 2000) 1200 c.1583C>G 9 p.T528R Missense Tail (Ig-fold) (Fokkema, et al, 2005;Vytopil, et al, 2003) (Bakay, et al, 2006;Young, et al, 2005) 51 c.1930C>T 11 p.R644C Missense Tail (Lamin A specific) (Csoka, et al, 2004;Genschel, et al, 2001;Mercuri, et al, 2005;Muntoni, et al, 2006;Pasotti, et al, 2008;…”
Section: F O R P E E R R E V I E Wmentioning
confidence: 99%
“…In fact, it has been suggested that lipodystrophies are etiologically linked to polycystic ovary syndrome [17] and, in isolated publications, to some obstetric complications [18]. In milder forms of the disease, the phenotype may be indistinguishable from the regular metabolic syndrome.…”
Section: Dunnigan-type Lipodystrophy Phenotype Assessmentmentioning
confidence: 99%